Physiological and electromyographic responses at three levels of bicycle seat height - Chen, Y. L.; Huang, H. W.; Chen, P. H.; Lee, Y. M.; Lee, H. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Recently, bicycle riding has become one of the most popular exercises. As the use time increased, the risk of pedalling injury raised. Holmes (1994) indicated that inappropriate bicycle saddle height could result in lower limbs injuries. The motivation of this study was to find out the best riding position that could effectively use energy from the physiology and electromyography measures. The oxygen consumption (VO2), heart rate (HR), respiratory exchange ratio (RER) and the muscle activity (electromyography, EMG) from rectus femoris (RF) and biceps femoris (BF) of lower limb were collected during a 6 min cycling trail in three different heights of bicycle saddle. The purpose of this study was to compare the effects of three different types of bicycle seat heights and different perspectives of muscle activity and physiology's parameters.